2022
DOI: 10.1186/s13047-022-00520-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the windlass mechanism on kinematic and kinetic foot joint coupling

Abstract: Background Previous research shows kinematic and kinetic coupling between the metatarsophalangeal (MTP) and midtarsal joints during gait. Studying the effects of MTP position as well as foot structure on this coupling may help determine to what extent foot coupling during dynamic and active movement is due to the windlass mechanism. This study’s purpose was to investigate the kinematic and kinetic foot coupling during controlled passive, active, and dynamic movements. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…They also showed that there is minimal elongation in the plantar aponeurosis as the heel rises, supporting the presence of a windlass mechanism during parts of stance. However, as also reported by Caravaggi et al (2010) and Williams et al (2022), the plantar aponeurosis shortens rapidly as the arch recoils in mid to late stance, suggesting a decline in tension (Williams et al, 2022).…”
Section: (6) Windlass Mechanismsupporting
confidence: 77%
See 3 more Smart Citations
“…They also showed that there is minimal elongation in the plantar aponeurosis as the heel rises, supporting the presence of a windlass mechanism during parts of stance. However, as also reported by Caravaggi et al (2010) and Williams et al (2022), the plantar aponeurosis shortens rapidly as the arch recoils in mid to late stance, suggesting a decline in tension (Williams et al, 2022).…”
Section: (6) Windlass Mechanismsupporting
confidence: 77%
“…(2010) and Williams et al . (2022), the plantar aponeurosis shortens rapidly as the arch recoils in mid to late stance, suggesting a decline in tension (Williams et al ., 2022).…”
Section: Historical Emergence Of Foot Function Paradigmsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, including deformation data as a predictor of mechanical function, results in drastically reduced accuracy. This could be because the shape deformations under static loading are not as closely related to locomotor function (Farris et al, 2020;Sichting and Ebrecht, 2021;Welte et al, 2018;Williams et al, 2022) as shape alone appears to be. Additionally, the added inter-subject variability and potential noise from unloaded foot shape contained in the deformation data (Schuster et al, 2021) may also contribute to the reduced predictive accuracy.…”
Section: Predicting Foot Function From Shapementioning
confidence: 99%